SOCS3 Expression by Thymic Stromal Cells Is Required for Normal T Cell Development - Gao, Yu; Liu, Ruining; He, Chenfei; Basile, Juan; Vesterlund, Mattias; Wahren-Herlenius, Marie; Espinoza, Alexander; Hokka-Zakrisson, Cassandra; Zadjali, Fahad; Yoshimura, Akihiko; Karlsson, Mikael; Carow, Berit; et al. (Frontiers in Immunology, 2021)
The suppressor of cytokine signaling 3 (SOCS3) is a major regulator of immune responses and inflammation as it negatively regulates cytokine signaling. Here, the role of SOCS3 in thymic T cell formation was studied in Socs3fl/flActin-creER mice (Δsocs3) with a tamoxifen inducible and ubiquitous Socs3 deficiency. Δsocs3 thymi showed a 90% loss of cellularity and altered cortico-medullary organization. Thymocyte differentiation and proliferation was impaired at the early double negative (CD4-CD8-) cell stage and apoptosis was increased during the double positive (CD4+CD8+) cell stage, resulting in the reduction of recent thymic emigrants in peripheral organs. Using bone marrow chimeras, transplanting thymic organoids and using mice deficient of SOCS3 in thymocytes we found that expression in thymic stromal cells rather than in thymocytes was critical for T cell development. We found that SOCS3 in thymic epithelial cells (TECs) binds to the E3 ubiquitin ligase TRIM 21 and that Trim21−/− mice showed increased thymic cellularity. Δsocs3 TECs showed alterations in the expression of genes involved in positive and negative selection and lympho-stromal interactions. SOCS3-dependent signal inhibition of the common gp130 subunit of the IL-6 receptor family was redundant for T cell formation. Together, SOCS3 expression in thymic stroma cells is critical for T cell development and for maintenance of thymus architecture.